Implementasi Rehabilitasi Terhadap Pengguna Narkotika (Studi Pada Badan Narkotika Nasional Provinsi Sumatera Utara) - Haga Septian Sembiring; Anggreni Atmei Lubis; Arie Kartika (Universitas Medan Area, 2021)
The problem of narcotics has now penetrated all elements of the nation, rehabilitation of narcotics addicts is a treatment process to free addicts from addiction. The implementation of rehabilitation by BNNP North Sumatra has an effect on narcotics handling more clearly and in a coordinated manner, and more young people are saved from narcotics due to undergoing rehabilitation. The factors that form the basis of North Sumatra's BNNP in implementing rehabilitation for narcotics users consist of internal and external factors. Internal factors, namely Human Resources (HR) which are still minimal and / or still lacking, facilities and infrastructure in the investigation section are still limited, including investigator unit cars, communication facilities or tapping devices, sniffer dogs and firearms personnel. The external factor is that other government agencies still assume that P4GN is only the duty of the National Narcotics Agency and the National Narcotics Narcotics Unit so that it seems that there is omission from the agency and the reluctance of the public to report to the police and the National Narcotics Agency even though there are people around the neighborhood involved in narcotics trafficking.